Effects of methionine and tryptophan on some quantitative traits of silkworm, Bombyx mori L. (Lepidoptera : Bombycidae) - Laz, Rezina (University Journal of Zoology, Rajshahi University, 2010)
The present experiment was carried out to determine the effects of methionine and tryptophan on some quantitative traits of silkworm, Bombyx mori L. Mulberry leaves were treated with 250,500,750 and 1000 ppm of amino acids and were provided to the worms as food. Compared to the controls amino acids (especially 500 and 750 ppm) significantly increased the fecundity, fertility, adult emergence, developmental periods and longevity of B. mori adults but decreased the mortality. Key words: Amino acids; Bombyx mori; fecundity; mortality; longevity. DOI: 10.3329/ujzru.v28i0.5280 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 15-19